Leadership Competencies for Quality Education in Rural Primary Schools of Ethiopia: The Case of Amhara and Oromia Regional States - Mulatu Dea Lerra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study examined the state of leadership competencies in ensuring quality education in selected schools of Amhara and Oromia regional states. In this regard, 36 schools from 10 Woredas, 5 from eeach region, were chosen purposively. 470 teachers and students, 36 head school principals, and 10 administrators were included in the study. Quantitative data was collected from respondents in blended form. Inferential statistics such as correlation, t-test, Principal Component Analysis (PCA), KMO, Bartlett’s Test of Sphericity (Chi-Square), and factor stacking and regression analyses were used to analyse the data. It was found that there was strong, positive, and statistically significant relationship and effect of leadership competencies on enhancing quality education. Based on the findings, it was recommeneded the need to develop and run leadership improvement program, have professional enlistment, develop new leadership policy, and establish leadership selection system in both regional states to achieve and maintain quality leadership and education.